Impact of distributed generation on nodal prices in hybrid electricity market. (2018) - Kumar, Manish; Kumar, Ashwani; Sandhu, K.S.
Abstract: Wind power integration in electrical utilities all over the world is increasing manifold due to environmental degradation concerns, technological innovations in turbine technology, smart grid initiatives, and competitive electricity market operation. In this paper, impact of distributed generation is presented on fuel cost and nodal prices in mix of pool and bilateral electricity market. In this paper, the main contributions are: (i) Mixed integer nonlinear programming (MINLP) approach for determining optimal location and number of distributed generators (ii) impact of wind power output on nodal prices of real and reactive power with wind power variation during 24 hours. The proposed MINLP based optimization approach has been applied for IEEE 24 bus reliability test system.